INNOVATION IN LEARNING PROPORTION USING PROPORTION TABLE - Oktaviani, Maya (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2019)
This study aims to develop learning of direct and inverse proportion by using proportion tables based on Pendidikan Matematika Realistik Indonesia (PMRI) approach. Data were collected from preliminary test results, classroom observation, field notes, student activity sheets, test answer sheets, and interviews conducted on students grade VII at Islamic Junior High School Al-Azhar 12 Rawamangun. Based on the results of the retrospective analysis, PMRI characteristics have a role in developing direct and inverse proportion. Students’ activities in observing the context presented can train students to develop learning strategies and explore the use of proportion tables. The proportion table can present the students’ informal thinking processes and assist students in solving problems related to direct and inverse proportion. The use of student construction results in each meeting contributes to assisting students in understanding the direct and inverse proportion. The conceptual relevance of this study attracts students’ attention because the context is given close to student life. Thus, the proportion table can help students to understand the proportion so that they can resolve the proportion problems.